BANGUNAN HIJAU VS BANGUNAN NON HIJAU Studi pada Gedung Utama Kementerian Pekerjaan Umum dan Gedung Juanda II Kementerian Keuangan - , Denny Setyaji P.; , Prof. Bambang Riyanto L.S., M.B.A., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Until recently, the adoption of green building concept as government office building in Indonesia is still very low due to the lack of knowledge of the stakeholders and the lack of supporting evidences related to green building performance. This study aims to indentify the performance of green building compared with non green building from the consumption of energy and water, the perception of occupant satisfaction and comfort, and the life cycle cost. Objects in this study are Utama Building Ministry of Public Works as a green building and Juanda II Building Ministry of Finance as a non green building. The data used are the consumption of energy and water, the survey of occupant satisfaction and comfort, and all of the incurring costs related to the building ownership and operation. Using sustainability theory, this study analyze the consumption of energy and water to represent the environmental side, analyze the occupant satisfaction and comfort to represent the social side, and analyze the life cycle cost to represent the economic side. The result shows that green building performance is better than non green building performance. Green building is proven to be more energy and water efficient, generating higher occupant satisfaction and comfort, and requiring lower life cycle cost when compared to non green building.